IMPROVEMENT OF UAV NOISE DIRECTION FINDING SYSTEMS USING VECTOR-PHASE METHODS AND SUPERDIRECTION - КОЗАК, А. В.; КОРЖИК, О. В. (Technologies and Engineering, 2023)
Purpose. Increasing the detection range of noise direction finding systems by providing the acoustic antenna with properties to ensure the registration of both scalar and vector characteristics of the acoustic field. Methodology. The use of vector-phase methods that ensure the formation of directivity characteristics in the area of lower frequencies. Findings. It was determined that the use of vector-phase receivers leads to the formation of the directivity characteristics of discrete interference antennas in the region of lower frequencies and makes it possible to obtain a unidirectional antenna without changing the design. At the same time, it was determined that the main characteristics of the acoustic field formed by the antenna are: pressure and oscillating speed. The theoretical foundations of the construction of noise direction finding systems have been defined. A multi-component vector acoustic antenna for detection and direction finding devices has been developed. Originality. The possibility of improving the systems of air and hydroacoustic noise direction finding due to the use of superdirectionality effects and vector-phase methods has been established. A multi-component vector acoustic antenna for detection and direction finding devices is proposed. It was determined that the implementation of vector-phase methods leads to the fact that the antenna maintains or improves the signal-to-noise ratio in the tasks of receiving acoustic signals in the air. In this way, a combination of discrete interference antennas is provided, which register not only the pressure field, but also the oscillating velocity field. Practical value. The proposed theoretical propositions can be used for the development of sound direction finding acoustic complexes for both air and hydroacoustic purposes. The proposed multi-component vector acoustic antenna of detection and direction finding devices implements a full set of measures for detecting and determining the angular coordinates of the target and can be used in noise direction finding acoustic complexes.